'Green and clean?' Hydropower between low-carbon and high social and environmental effects - Karen Meijer; Waltina Scheumann; Daniel Däschle; Ines Dombrowsky (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
During the last decade, hydropower has made a remarkable return to the global agenda, after having been absent due to heavy criticism because of its social and environmental impacts. The proponents of hydropower development claim that hydropower is 'clean' and 'green' and can thus support low-carbon development paths. Combating climate change requires electricity generation from sources with low greenhouse gas emissions (GHG), and because hydropower is a low emitter, it has the potential to contribute to the protection of a global public good: the global climate, and to foster economic growth and social development. It is this potential which brought hydropower back to centre stage. However, the role hydropower can play in mitigating global climate change creates a dilemma: Is hydropower desirable because of its ability to provide low-carbon energy, or undesirable because of its local environmental and social impacts? The answer is neither straightforward nor simple, and difficult decisions have to be made. There is no doubt that global warming is the major threat of this century. But local social and environmental impacts of hydropower schemes continue to exist, and the more positive view on hydropower carries the risk that the negative impacts – on people and on resources – are overlooked. These impacts should not be set aside too easily because of the benefits of low-carbon growth. With all knowledge and experience gained, the renewed attention to hydropower also provides an opportunity: the opportunity to develop and operate dams in a more socially and environmentally friendly way. Given that hydropower can play a role in providing affordable and flexible renewable energy, the overall aim should be to choose the least bad or lowest impact option for providing affordable and lowcarbon electricity. National agencies should be supported in order to ensure a wellinformed and equitable balance between global and local benefits and costs. Whether one likes it or not, hydropower will feature in many energy development and climate mitigation plans in this century. Let us use this momentum to develop hydropower the right way.
Keywords: 330; Klimawandel; Energie